Kriminalisasi Korban Sextortion Dalam Pasal 27 Undang-Undang Informasi Dan Transaksi Elektronik (Uu Ite) Dan Perspektif Hukum Pidana Islam - Maftuh Ihsan Sofa; Akmaluddin Syahputra (Universitas Muhammadiyah Mataram, 2026)
This study examines the potential criminalization of sextortion victims under the application of Article 27 of the Indonesian Electronic Information and Transactions Law (EIT Law) from the perspective of Islamic criminal law. The background of this research is the increasing prevalence of sexually based cybercrime driven by technological development, where sextortion victims not only suffer from extortion and threats but also risk being treated as perpetrators of morality offenses due to the transmission or distribution of intimate content under coercion. This research employs a normative legal research method using statutory, conceptual, and comparative approaches between positive law and Islamic criminal law. The legal materials consist of primary, secondary, and tertiary sources analyzed through qualitative normative analysis. The findings indicate that Article 27 paragraph (4) of the EIT Law provides a legal basis for prosecuting sextortion as an electronic-based extortion and threat offense. However, the application of Article 27 paragraph (1) may lead to the criminalization of victims due to a formalistic interpretation that neglects coercion and psychological pressure. From the perspective of Islamic criminal law, sextortion victims cannot be held criminally responsible as they act under ikrah (coercion), and the offense is categorized as ta’zir, which places full responsibility on the perpetrator.